Seromucinous hamartoma with unique clinical and histopathological features: a case report and review of the literature - Mikhael Makhoul; Nadim Khoueir; Myriam Khneisser; Hussein Nassereddine (Journal of Medical Case Reports, 2024)
Abstract Background We present this case to highlight the importance of considering seromucinous hamartoma in the differential diagnosis of nasal cavity lesions, particularly due to its rarity and potential for being mistaken for more aggressive pathologies. Seromucinous hamartoma, although benign, can exhibit clinical and histological features that overlap with those of malignant tumors, posing a diagnostic challenge. This case is especially noteworthy due to the unusual presentation of sebaceous differentiation within seromucinous hamartoma, a feature not previously documented in the literature. Recognizing such rare entities is crucial for ensuring appropriate patient management and avoiding unnecessary interventions. Case presentation We report a unique case of a 41-year-old Caucasian man with seromucinous hamartoma, presenting with chronic left nasal obstruction and recurrent mild epistaxis. Nasal endoscopy revealed a well-defined, multilobulated lesion in the left nasal cavity. Computed tomography scans confirmed an anteromedial polypoid lesion, 31 mm × 15 mm. The lesion was endoscopically resected without complications, with no recurrence at 6-month follow-up. Pathological examination showed a filiform polypoid lesion with clusters of seromucinous glands, ducts, and tubules, and no invasive growth patterns. Immunohistochemical studies revealed distinct epithelial membrane antigen (EMA) and p63 staining patterns. Notably, mature sebaceous gland formation interspersed with seromucinous glands was observed, a novel finding in seromucinous hamartoma. Recognizing seromucinous hamartoma is crucial to avoid unnecessary treatments, and it should be included in differential diagnoses of nasal cavity lesions. Conclusion Seromucinous hamartoma is a rare and benign nasal cavity lesion that presents significant diagnostic challenges due to its potential to mimic more aggressive pathologies. This case highlights the importance of including seromucinous hamartoma in the differential diagnosis of sinonasal lesions, particularly when unusual histological features, such as sebaceous differentiation, are present.